MOTHER EDUCATES: QUESTIONING MOTHER’S CARE CAPACITY FOR SCHOOL-AGE CHILDREN - Meilanny Budiarti Santoso; Nurliana Cipta Apsari; Budi Muhammad Taftazani (Share : Social Work Journal, 2022)
Parenting is a two-way interaction process between parents and children that is influenced by the culture and social institutions in which children are raised. Exploring factors that influence the ways mothers in parenting the children is the focus of this study. The research conducted in qualitative method with a descriptive research design. In-depth interviews, focus group discussions and observations, were the methods used by researchers to gather information from informants. The results show that age, education level, parenting experience received by parents, and the birth order of children contributed to the mother's care process. Using a framework of internal/external driving factors, and internal/external inhibiting factors the researchers chart the influences on mothers’ parenting practices. The researchers recommend developing a local community of mothers as an important strategy for learning and sharing experiences in parenting.